Avaliação de pulverizadores hidráulicos de barra na região de Uberlândia-MG - Alvarenga, Cleyton Batista de (2009)
Any and every manner of pesticide application represents environmental risks, which must be minimized by the use of proper knowledge and technology, assuring a sustainable food production. Often, great importance is given to the pesticide and little to the application technique. The identification of the conservation state and mode of use of the sprayers in agriculture can direct new research and investment for the maintenance and adequate use of such equipment, thus contributing for the reduction of costs and environmental contamination. Therefore, this study evaluated the operational state of agricultural sprayers in the region of Uberlândia, Minas Gerais, and the need to implement periodical inspection programs for sprayers, developing specific evaluation methods for Brazilian conditions. The evaluations were done in farm properties randomly visited and consisted of a questionnaire filled out by the machine operator and of the inspection of the equipment. The following items were evaluated: presence of leakage; conservation state and location of the hoses; presence and conservation state of the line filters, nozzle; presence and conservation state of anti-drippers; regularity and nozzle spacing; similarity of spray nozzles in the boom; presence, operability, adequacy and precision of the manometer; protection of mobile parts; errors in the application volume; uniformity of volume distribution in the boom; nozzle flow; rotation at the tractor power take-off; machinery age; coupling form; boom lifting systems; orientation by band and monitoring the environment conditions. This study diagnosed the boom sprayers condition in the region. This information served as the basis to recommend the implementation of a regional program of periodical evaluation of boom sprayers. The results indicated the need to implement a frequent evaluation program for this equipment, to meet the consumer market that is concerned with food quality, the environment and well being of the laborers. Every sprayer evaluated had problems, and the most frequent were: non uniformity of product distribution along the boom, lack of monitoring of environmental conditions before and during spraying, inadequate conservation state of nozzles and mistakes on the mixture volume applied. Many incompatibility adjustments found, often, are easily fixed and low cost, without any reason of being omitted. The repetition of the evaluations in subsequent years is fundamental to monitor the response of farmers in relation to acceptance of suggestions made by the technician, and to monitor improvements in the equipment. The method used was adequate to evaluate the working conditions of the agricultural sprayers, except for the mixture distribution uniformity along the boom, which is made with graduated cylinders, making clear the negative effect of wind affecting the results.